Synthesis and hypoglycemic activity of 7-n-butyl-3-methyl-8-thioxanthine derivatives - M. I. Romanenko; D. G. Ivanchenko; T. A. Sharapova; I. M. Bilay; K. V. Aleksandrova (The State Expert Center of the Ministry of Health of Ukraine, 2018)
According to the International Diabetes Federation in 2015 were registered 59.8 million patients with diabetes in Europe. Synthetic drugs are widely applied in addition to a variety of insulins to normalize blood glucose level. It should be noted that the oral anti-diabetic drugs are the common therapeutic agents for the treatment of diabetes mellitus type II, and therefore the search for new non-toxic hypoglycemic agents is one of the most urgent problems of modern pharmaceutical science. It is known that 7,8-disubstituted xanthine derivatives exhibit hypoglycemic activity. The aim of this work lies in developing unique method to synthesize undocumented in other scientific papers 7-n-butyl-3-methyl-8-thioxanthine derivatives and also studying of their hypoglycemic activity. Acute toxicity of synthesized compounds has been studied with the application of Prozorovsky's method. The glucose homeostasis characteristic has been performed on carbohydrate tolerance that has been determined by the glucose load test on the control group and on the intact rats. The reactions of 7-n-butyl-3-methyl-8-thioxanthine with benzylchlorides, bromoketones, esters and an amide of chloroacetic acid have been studied. Reactions of mentioned syntons proceed smoothly in aqueous propanol-2 environment and lead to the formation of the corresponding 8-benzyl-, benzoylmethylthioxanthines and xanthinyl-8-thioacetic acid derivatives. Accessible laboratory method has been elaborated to synthesize unspecified in scientific papers earlier 8-thiosubstituted 7-n-butyl-3-methylxanthine by reacting 7-n-butyl-3-methyl-8-thioxanthine with benzylchlorides, bromoketones, esters and an amide of chloroacetic acid, their structure having been proved by NMR-spectroscopy data. The acute toxicity of synthesized compounds has been studied. It has been established that LD50 is in the range 820-2477 mg/kg, i. e. obtained substances are low-toxic and practically non-toxic according to Sidorov's classification. Also the study of hypoglycemic activity of synthesized compounds has been carried out. A significant perspective for further research to find the original antidiabetic agents has been shown by bioassay results. It has been found that 7-n-butyl-3-methylxanthinyl-8-thioacetamide is more active than reference substances.